2003
DOI: 10.1046/j.1365-2036.2003.01519.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐steroidal anti‐inflammatory drugs, aspirin and newly diagnosed colitis: a case–control study

Abstract: SUMMARYBackground: There have been a number of reports of colitis following exposure to non-steroidal anti-inflammatory drugs (NSAIDs) and salicylates. Aim: To conduct a case-control analysis of new cases of colitis, with particular reference to the usage of NSAIDs and salicylates prior to the development of the disease. Methods: One hundred and five consecutive new cases of colitis presenting to a single gastroenterologist were questioned about their recent usage of NSAIDs and salicylates. For comparison, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
3
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 41 publications
3
33
3
4
Order By: Relevance
“…NSAIDs in general, and ASA in particular, are known to have a harmful effect on the gastrointestinal tract. NSAIDsrelated colitis has been described in connection with both short- [12,22] and long-term treatments [23] . Different clinical observations and case-control studies have linked the use of NSAIDs or salicylates to diagnosis of acute diarrhea syndrome [24] and exacerbation of inflammatory colitis (ulcerative colitis or Crohn's disease) [23] .…”
Section: Discussionmentioning
confidence: 99%
“…NSAIDs in general, and ASA in particular, are known to have a harmful effect on the gastrointestinal tract. NSAIDsrelated colitis has been described in connection with both short- [12,22] and long-term treatments [23] . Different clinical observations and case-control studies have linked the use of NSAIDs or salicylates to diagnosis of acute diarrhea syndrome [24] and exacerbation of inflammatory colitis (ulcerative colitis or Crohn's disease) [23] .…”
Section: Discussionmentioning
confidence: 99%
“…cause inflammatory lesions in the small intestine in about 60% of patients using them long term (Smale et al, 2001), and as many as 75% of patients with erosive colitis are chronic NSAIDs users (Gleeson and Davis, 2003). NSAIDs induce peptic ulceration and injury to the small and large intestine causing increased permeability with protein and blood loss and stricture formation (Hawkey, 1993;Rainsford, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…ciated colitis has been associated to both short term [21,23] and long term treatments [22]. In our series we can not determine if there is any relation between the onset of I.C.…”
Section: Discussionmentioning
confidence: 70%
“…NSAIDs and salycilates have been largely associated to several forms of colitis, including I.C [21][22][23]. Studies in the TNBS model confirmed the ability of NSAIDs to exacerbate colitis [24].…”
Section: Discussionmentioning
confidence: 99%